Kicking in or kicking out? The role of the individual motor expertise in predicting the outcome of rugby actions - Paolini, Simone; Bazzini, Maria Chiara; Rossini, Marco; De Marco, Doriana; Nuara, Arturo; Presti, Paolo; Scalona, Emilia; Avanzini, Pietro; Fabbri-Destro, Maddalena (Frontiers in Psychology, 2023)
In sports, understanding others' actions represents a fundamental skill that allows players to predict the outcome of teammates’ and opponents' actions and counteract them properly. While it is well known that motor expertise sets better premises for predicting the result of an observed sports action, it remains untested whether this principle applies to a team where players cover different positions that imply different motor repertoires. To test this hypothesis, we selected rugby as a paradigmatic example in which only one or two players out of 22 train and perform placed kicks. We administered a placed kick outcome prediction task to three groups of participants, namely, rugby kickers, rugby non-kickers, and controls, thus spanning over different combinations of motor expertise and visual experience. Kickers outperformed both their non-kicking teammates and controls in overall prediction accuracy. We documented how the viewpoint of observation, the expertise of the observed kicker, and the position of the kick on the court influenced the prediction performance across the three groups. Finally, we revealed that within rugby players, the degree of motor expertise (but not the visual experience) causally affects accuracy, and such a result stands even after accounting for the level of visual experience. These findings extend the role of motor expertise in decoding and predicting others' behaviors to sports teammates, among which every member is equipped with a position-specific motor repertoire, advocating for new motor training procedures combining the gestures to-be-performed with those to-be-faced.